Analysis of Performance Losses Related to Shaft Angle on Fishing Boats Using the Free Running Model Test Method - Aang Wahidin; Rachmad Tri Soelistijono; Fitri Hardiyanti; Lilik Subiyanto; Gaguk Suhardjito; Subagio So’im (International Journal of Marine Engineering Innovation and Research, 2023)
Several traditional fishing boats in Sendang Biru, Malang Regency are of the sekoci type using an inboard engine drive system with the position of the propeller shaft installed at an angle to the ship's base line. Based on the theory can reduce the performance of the ship propulsion system up to (2-3)%. In this research, we analyzed how much performance was lost/decreased on the lifeboat type fishing boats installed above. The method we use is the Free Running Model Test by making a model of a traditional fishing boat type of lifeboat with a model size of Loa = 100 cm, Lwl = 80.72 cm, B = 19.7 cm, H = 10.68 cm and T = 5, 08 cm made of aluminum sheet. The Free Running Model Test uses 1 motor and propeller which has a thrust of 60 watts, remote control equipment uses the main component of the NRF24L01 transceiver which works at a frequency of 2.4 Ghz with a range of 240 meters to 1 kilometer with conditions without obstacles and camera equipment drone to record the track. The results of this study show that there is a decrease/loss of performance at a 3-degree angle of 0.24%, at a 5-d. gree angle of 0.49%, at a 10-degree angle of 2.52%, at a 15-degree angle of 4.41% and at an angle of 20 degrees of 6.48%.